Ion desorption from molecules condensed at low temperature: A study with electron-ion coincidence spectroscopy combined with synchrotron radiation - Kazuhiko Mase; Mitsuru Nagasono; Shin-ichiro Tanaka; Tetsuji Sekitani; Shin-ichi Nagaoka (Физика низких температур, 2003)
This article reviews our recent work on photo-stimulated ion desorption (PSID) from molecules condensed at low temperature. We have used electron-ion coincidence (EICO) spectroscopy combined with synchrotron radiation. The history and present status of the EICO apparatus is described, as well as our recent investigations of condensed H₂O, NH₃, CH₃CN, and CF₃CH₃. Auger electron photoion coincidence (AEPICO) spectra of condensed H₂O at the O:1s ionization showed that H⁺ desorption was stimulated by O:KVV Auger processes leading to two - hole states (normal- Auger stimulated ion desorption (ASID) mechanism). The driving forces for H⁺ desorption were attributed to the electron missing in the O - H bonding orbitals and the effective hole-hole Coulomb repulsion. The normal ASID mechanism was also demonstrated for condensed NH₃. The H⁺ desorption at the 4a₁ ← O(N):1s resonance of both condensed H₂O and condensed NH₃ was found to be greatly enhanced. Based on the AEPICO spectra the following four-step mechanism was proposed: (1) the 4a₁ ← 1s transition, (2) extension of the HO - H (H₂N - H) distance within the lifetime of the (1s)⁻¹(4a1)¹ state, (3) spectator Auger transitions leading to (valence)⁻²(4a₁)¹ states, and (4) H⁺ desorption. The enhancement of the H⁺ desorption yield was attributed to the repulsive potential surface of the (1s) - 1(4a₁)¹ state. At the 3p ← O:1s resonance of condensed H₂O, on the other hand, the H⁺ yield was found to be decreased. The AEPICO spectra showed that the H⁺ desorption was stimulated by spectator Auger transitions leading to (valence)⁻²(3p)¹ states. The decrease in the H⁺ yield was attributed to a reduction in the effective hole-hole Coulomb repulsion due to shielding by the 3p electron. Photoelectron photoion coincidence (PEPICO) spectra of condensed H₂O showed that the core level of the surface H₂O responsible for the H⁺ desorption was shifted by 0.7 eV from that of the bulk H₂O. The H⁺ desorption from condensed CH₃CN was also investigated. In a study of condensed CF₃CH₃ using PEPICO spectroscopy, site-specific ion desorption was directly verified; that is, H⁺ and CH₃⁺ desorption was predominant for the C:1s photoionization at the -CH₃ site, while C₂Hn⁺, CFCHm⁺, and CF₃⁺ desorption was predominantly induced by the C:1s photoionization at the -CF₃ site. These investigations demonstrate that EICO spectroscopy combined with synchrotron radiation is a powerful tool for studying PSID of molecules condensed at low temperature.